Necessity Historically Considered - Schwartz, Daniel (Journal of moral philosophy, 2020)
Abstract The principle of necessity as applied to self-defence requires the use of the least harmful defensively effective means of thwarting a wrongful threat. Yet –so I argue – a harm can be excessive even when it is the least harmful way of dealing with the threat at the time of the attack. I therefore propose a historical view of the requirement of necessity. Historical necessity requires the selection of the least harmful means to thwart a future attack at the point in time at which we have a solid presumption that the future attack will take place. This may happen considerably before the time of the attack. Once you fail to acquire or preserve the least harmful defensive option for thwarting a future attack you may come to be irrevocably in breach of necessity. The paper tackles a number of objections to the view proposed.